2023
DOI: 10.1111/ene.15828
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic distribution of isolated abducens nerve palsy: Analysis of 807 patients and literature review

Abstract: Background and Purpose The etiologies of abducens nerve palsy have shown a large variability among studies. This study aimed to establish the clinical features and underlying etiologies of isolated abducens nerve palsy by recruiting patients from all departments in a referral‐based university hospital. Methods We reviewed the medical records of 807 patients with a confirmed diagnosis of isolated abducens nerve palsy at all departments of Seoul National University Bundang Hospital, Seongnam, Republic of Korea, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
(101 reference statements)
1
5
1
Order By: Relevance
“…This finding is similar to that observed in our previous studies on isolated trochlear and abducens palsies [18,19]. However, the proportion of involved specialists differed markedly amongst the isolated ocular motor nerve palsies (Figure 6c).…”
Section: Ta B L Esupporting
confidence: 91%
See 4 more Smart Citations
“…This finding is similar to that observed in our previous studies on isolated trochlear and abducens palsies [18,19]. However, the proportion of involved specialists differed markedly amongst the isolated ocular motor nerve palsies (Figure 6c).…”
Section: Ta B L Esupporting
confidence: 91%
“…The etiological distribution of isolated oculomotor nerve palsy observed in this study was significantly different from that of the data pooled from the previous reports with a higher prevalence of neoplastic etiology and lower prevalence of microvascular, idiopathic and traumatic etiologies. Our previous study also showed etiologies of isolated abducens nerve palsy that were different from those of the previous studies [19]. These findings seem to be related to a referral bias since our hospital is less frequently involved in the management of traumatic patients.…”
Section: Ta B L Econtrasting
confidence: 59%
See 3 more Smart Citations